Curating the Christian arts of Asia: global art histories at the Asian civilisations museum - Meegama, Sujatha Arundathi (2022)
This essay examines the transformation of the Asian Civilisations Museum (ACM) into a global art histories museum. An analysis of the new Christian Art Gallery and its objects that date from the eighth through the twentieth century illuminates the ways in which the ACM engages with global art histories in a permanent gallery and not only through special exhibitions. This essay begins with a history of the ACM and its transition from a museum for the “ancestral cultures of Singapore” to one with a new mission focusing on multicultural Singapore and its connections to the wider world. Hence, taking a thematic approach, the ACM's new galleries question how museums generally display objects along national lines or regional boundaries. This essay also brings attention to the multiple mediums and functions of Christian art from both the geographical locations that usually are associated with Asian art and also from cultures that are rarely taught or exhibited, such as TimorLeste, the Philippines, Sri Lanka, and Vietnam. While showcasing the diferent moments that Christianity came to Asia, the museum also emphasizes the agencies of Asian artistic practitioners in those global encounters. Although appreciative of the ways in which the ACM's Christian Art Gallery reveal the various tensions within global art histories and break down hegemonic constructions of Christian art from Asia, this essay also ofers a critique. Highlighting this unusual engagement with Christian art by an Asian art museum, the new gallery reveals that museums and exhibitions can add to the conversations on global art histories.